Krisis Religiusitas Pemuda di Era Digital: Strategi Manajemen Dakwah Berbasis Media Sosial - thoriq khoirunnas; Hari Santoso Wibowo; Fathurrahman Masrukan (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This research aims to study da’wah management strategies in facing the crisis of youth religiosity in the digital era through a literature review approach. Data were gathered from various scientific journals and academic articles related to digital da’wah, social media, and youth religiosity. The results reveal that digital da’wah on YouTube, Instagram, and TikTok is effective in reaching young audiences due to its flexibility, interactivity, and ease of access. However, the effectiveness of digital da’wah is determined by the quality of content, communication strategies, and the level of the youth’s digital literacy. Therefore, it is necessary to have adaptive and contextual da’wah management strategies to strengthen the religiosity of the youth in the midst of the rapid development of technology.